Pengaruh Permodalan CSR terhadap Pengembangan Usaha UMKM Mitra Binaan PT. LEN Industri (Persero) Kota Bandung - Novianti, Fitria; Adji, Widwi Handari (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study was carried out at PT Len Industri with the intention of examining the impact of corporate social responsibility (CSR) capital on MSME business development of Assisted Partners Pt. Len Industri (Persero) Bandung City, which is documented at the company PT Len Industri. In this study, a sample size of 37 Assisted MSEs was used to represent the population of 200 MSE Assisted Partners of PT Len Industri. A Likert scale is employed in the methodology, which is quantitative. In order to assess the validity of a study's findings and its reliability on the problems being examined, the data gathering approach employs samples from businesses that apply the Slovin formula. As evidenced by the (t) test study findings, the capital program The CSR Unit's work, which is largely carried out by PT Len Industri, has a substantial impact on the business growth of supported MSEs. by providing more capital help to MSME. The Social and Environmental Responsibility MSME Program gives priority to MSMEs that are still small but have the potential to grow. These MSMEs are developed through training and knowledge provision so that those who receive capital can use it properly and productively. Keywords: Capital, Business Development, MSMEs